Between Eleatics and Atomists: Gorgias’ Argument against Motion - Ioli, Roberta (Revista Archai, 2021)
The aim of my paper is to investigate Gorgias’ argument against motion, which is found in his Peri tou me ontos and preserved only in MXG 980a18. I tried to shed new light both on this specific reflection and on the reliability of Pseudo-Aristotle’s version. By exploring the so called “change argument” and the “argument from divisibility”, I focused on the particular strategy used by the Sophist in his synthetike apodeixis, which should be investigated in relation to the dispute between monistic and pluralistic ontology. In this regard, the puzzle from “divisibility everywhere” and its connection with the void as not-being can provide new elements to grasp the philosophical background in which the Sophist moves. On the one hand, Gorgias’ argument against motion is part of a broader dispute on the divisibility/indivisibility of being; on the other, his original elaboration of this puzzle seems to be perfectly understandable within the controversy between Eleatics and Atomists, and coherent with the argumentative style of the Sophist.